Effects of Vasoactive Intestinal Polypeptide and Forskolin on mRNA Expression of Prolactin and Prolactin Regulatory Element-Binding Protein in the Anterior Pituitary Gland of Chicken Embryo and Laying Hens - Norio Kansaku; Yasuko Tobari; Gen Hiyama; Shin Wakui; Naokazu Minoguchi; Masazumi Numata; Katsutoshi Kino; David Zadworny (The Journal of Poultry Science, 2016)
Vasoactive intestinal peptide (VIP) treatment induced mRNA expression of Prolactin (PRL) in the chicken anterior pituitary gland. VIP responsive element (VRE) of the PRL promoter was identified in the various bird species. However, transcription factor, which binds to VRE, has not yet been identified. Prolactin regulatory element-binding protein (PREB) gene cloned as a candidate transcription factor binds to VRE. Increases of mRNA levels of PRL and PREB during embryogenesis were identified. However, whether VIP affects levels of PRL and PREB mRNA during embryogenesis remains unknown. The effects of VIP and forskolin on mRNA expression of PRL and PREB in the embryonic anterior pituitary gland were assessed. Furthermore, administration of VIP to laying hens was conducted to examine the relationship between VIP and PREB mRNA expression. At day 14 of the embryonic growth stage, VIP treatment did not affect mRNA levels of either PRL or PREB, whereas forskolin treatment induced the increase of these mRNA levels. At day 20, both VIP and forskolin induced an increase of PRL and PREB mRNA levels. The administration of VIP significantly increased mRNA levels of PRL and PREB in the anterior pituitary gland of White Leghorn and Nagoya. These results indicate that the effects of VIP on PRL and PREB mRNA expression levels of VIP receptor may in turn affect PRL and PREB mRNA levels in the chicken anterior pituitary gland.